Delay in healthcare seeking and associated factors among patients presenting with sexually transmitted infection symptoms in the Horo Guduru Wollega Zone, Oromia, Western Ethiopia, 2022 - Guddu, Getachew Abebe; Getahun, Ayantu; Yadesa, Girma; Tolossa, Tadesse (Frontiers in Reproductive Health, 2024)
Background Sexually transmitted infections (STIs) are the most prevalent communicable diseases that impact people's health and wellbeing. One of the main obstacles to successful prevention and control of STIs is the delay in seeking healthcare, which can result in significant personal and economic losses. However, there are limited studies on the delay in healthcare seeking among STI patients in resource-limited countries such as Ethiopia. Objective This study aims to assess delays in seeking healthcare and associated factors among patients presenting with STIs at public health facilities in the Horo Guduru Wollega Zone, Oromia, Western Ethiopia, 2022. Methods A cross-sectional study was conducted at public health facilities in the Horo Guduru Wollega Zone from 15 March to 15 May 2022. The study included 507 participants and used a consecutive sampling method. The outcome variable of the study was the delay in seeking healthcare among STI patients. A binary logistic regression model was used to identify candidate variables with a p-value of less than 0.25 after analyzing each variable separately. Finally, a multivariable analysis was performed to determine statistically significant variables at a p-value of less than 0.05, and an adjusted odds ratio (AOR) was reported. Results The proportion of individuals with STIs who delayed seeking healthcare in the Horo Guduru Wollega Zone was 61.3% [95% confidence interval (CI): 57%–65.5%]. Factors such as age >35 years (AOR = 2.23, 95% CI: 1.26–3.95), higher educational level (AOR = 2.72, 95% CI: 1.55–4.74), lack of condom use (AOR = 1.63, 95% CI: 1.05–2.55), and travel time to health facilities of >1 h (AOR =<sans-serif> 4</sans-serif>.30, 95% CI: 1.70–10.89) were found to be significantly associated with delayed healthcare seeking. Conclusion and recommendations This study found that the magnitude of delay in seeking healthcare was higher than the national average and identified several contributing factors. Interventions such as developing educational programs and improving access to healthcare services are crucial for supporting patients with STIs. Enhancing healthcare accessibility in rural areas and promoting the use of condoms through targeted community outreach can reduce travel time and prevent delays in seeking healthcare for STIs.